Social accounting matrix: A user manual for village economies - Steven Gronau; Etti Winter (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
The application of Social Accounting Matrices (SAM) is well established at the national level and provides a comprehensive economic framework. The procedure for developing national SAMs is extensively documented in literature. However, it can also be constructed for smaller economies, such as a village. Studies dealing with village SAMs are rare. In addition, there are hardly any guidelines for design. This gap will be addressed in this paper, which provides a manual for the construction of a village SAM. Theoretical principles and data requirements are discussed. A hypothetical village SAM is constructed by using numerical examples. Subsequently, the SAM of a real-world village case study from Zambia is analyzed. It is demonstrated how macroeconomic indicators can be calculated and microeconomic information obtained. Furthermore, a village SAM provides the database for scientific modelling approaches which are presented. Village SAMs are thus a useful management tool and support policy planning at local and regional level.
Keywords: A33; E16; O21; R58; 330; Social accounting matrix; user manual; village economies; management tool; policy planning